TECHNOLOGICAL UNEMPLOYMENT IN CANADIAN AGRICULTURE - Ostershek, Helene Adele (My University, 1948)
In the past, several writers have expressed, with a great deal of undue pessimism, their ideas on "Technological Unemployment"; too many believe that eventually the world will evolve into a system of robots. The specific aspect of "Technological Unemployment", dealt with in this thesis, is that found in connection with Canadian agriculture. An attempt has been made to study the effects of the introduction of machinery, first, on the economy as a whole, and then on agriculture in the provinces of Canada and to demonstrate that the evils of the machine have largely been over-emphasized. I would like to thank Professor H. Michell for his valuable suggestions and constructive criticisms.
Keywords: Political Economy